Mixed-model production system design for aircraft assembly - Briggs, James; Jin, Yan; Price, Mark; Burke, Robert (Cranfield University Press, 2013)
With the advancement of flexible fixture and flexible tooling, mixed production has become possible for aircraft assembly as the manufacturing processes of different aircraft/sub-assembly models are similar. However, due to the low volume and complex constraints of aircraft assemblies, how to model the problem and produce a practical solution has been a great challenge. To tackle this challenge, this work proposes a methodology for designing the mixed production system, and a new scheduling approach is proposed by using combined backward and forward scheduling methods. These methods are validated through a real-life industrial example. As a result, the number of workstations is reduced by 50%, and the cycle time for making a fuselage is reduced by 38% by using the new mixed-model system.
Keywords: Mixed-model; Aircraft assembly; Production system design